The Acts of Thomas : introduction, text, and commentary - Klijn, Albertus Frederik Johannes (Supplements to Novum Testamentum, 2003)
This is the second edition of a book published as long ago as 1962. The at that time relatively young Dr. A.F.J. Klijn was brought up in the school of W.C. van Unnik and G. Quispel, both in Utrecht. In his book about the Acts of Thomas he tried to demonstrate that this work cannot be reckoned among the Gnostic writings but belongs to the early Syriac or rather Eastern Christian tradition. In the last decades much has been written about Syriac Christianity, which made it necessary to rewrite the original introduction of this book. The commentary has mainly been left as it was, although many additions have been made to its great number of valuable references.